(untitled) (Revista de História Regional, 2007)
The article discusses how the french geographer Pierre Monbeig elaborated the theme of bandeirante psychology as a fundamental feature in the zones of colonization of São Paulo and Paraná during the 30 and the 40’. In that context, when Estado Novos intellectuals were also using the image of the bandeirante to create a link with the past and justify the government migratory and land policies, Monbeig redefined that traditional figure in anti-authoritarian and individualistic terms.